2021
DOI: 10.37506/mlu.v21i2.2642
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Nurses Regarding Corona Virus (COVID-19): An Educational Intervention

Abstract: Background: COVID-19 it is the new coronavirus and most cases appeared in the Chinese city, Wuhan at the end of December 2019 in the form of acute pneumonia. It was identified through genetic sequences. It is believed that the originated in animals and most cases appeared in the seafood and animal market in Wuhan. The virus can spread from the infected person to another person through close contact without protection. Aim was to evaluate the effect of an educational intervention nurses' knowledge and practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These results confirmed by Egyptian study who found that about half of nurses (51.4%), their experience ranged from 5-10 years. (47.1%) of participants have (1-5) years of experience in isolation ward (6) .…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed by Egyptian study who found that about half of nurses (51.4%), their experience ranged from 5-10 years. (47.1%) of participants have (1-5) years of experience in isolation ward (6) .…”
Section: Discussionmentioning
confidence: 99%